THE ROLE OF LEADERSHIP IN PREVENTING GROUPTHINK IN ORGANIZATIONAL DECISION MAKING - Anggie Nur Fitrianti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Abstract Groupthink is a common situation in group decision-making, where the desire to reach consensus often overrides the critical evaluation of decision options. This phenomenon is more likely to occur in public organizations and bureaucracies that tend to be hierarchical and rigid. This study aims to identify the role of leadership in reducing the risk of groupthink through the Systematic Literature Review (SLR) method. Of the 32 articles analyzed, it was found that an authoritarian leadership style increases the risk of groupthink, while participatory, inclusive, transformational, vigilant, and ethical leadership styles have been shown to minimize this risk. This study contributes both academically and practically, particularly in understanding the relationship between leadership style and the potential for groupthink.